The Implementation of Emotion Puzzles to Support Religious Habituation in the Emotional Development of Children at RA Taqwa Liga Muslim Indonesia - Mutiara, Yolanda; S, Suparmita; Hidayah, Citra Ayu; Stiawan, Sakti (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service activity was conducted at RA Taqwa Liga Muslim Indonesia and aimed to implement the Emotion Puzzle as part of religious habituation to support children’s emotional development. The media was applied through play-based learning combined with guidance in religious values such as praying, apologizing, patience, and gratitude. The implementation methods included socialization, teacher assistance, classroom practice, and evaluation. The results showed that children were better able to identify basic emotions such as happiness, sadness, anger, and fear, and began to demonstrate religious-based behavior during daily interactions. Teachers also gained new skills in integrating emotional learning with religious values. Therefore, the Emotion Puzzle can serve as an effective and simple learning tool to support emotional development through a religious approach.